Firm R&D and financial analysis: How do they interact? - Goldman, Jim; Peress, Joel (Journal of Financial Intermediation, 2023)
This paper demonstrates, theoretically and empirically, that firms’ research and development (R&D) efforts and investors’ analyses of their prospects are mutually reinforcing. Entrepreneurs attempt more research when financiers are better informed about projects’ profitability because they expect financiers to provide more funding to successful projects. Conversely, financiers collect more information about projects when entrepreneurs undertake more R&D because the opportunity cost of missing out on successful projects is then higher. Two natural experiments confirm that this interaction occurs and suggest that it contributes to about one third of the total effect of a policy designed to stimulate R&D. Overall, the analysis suggests that policies aimed at promoting R&D – such as research subsidies or tax breaks – have a multiplier effect owing to the induced improvement in capital efficiency. As a result, those policies can be rendered more effective by coupling them with other policies designed to increase capital efficiency. The feedback effect that we document also helps explaining why innovative ecosystems such as that in the Silicon Valley are challenging to set up.